The Study of Living Qur'an on Al-Ma’tsurat Recitation Tradition at Darul Qur'an Islamic Boarding School Pendung Talang Genting: Studi Living Al-Qur’an pada Tradisi Pembacaan Al-Ma’tsurat di Pondok Pesantren Darul Qur’an Pendung Talang Genting (Takwil: Journal of Quran and Hadith Studies, 2022)
It takes calm in everything that we will do, especially when the students study religious knowledge, study Qur’an and memorize Qur’an. This gave birth to a thought to create a peaceful and serene atmosphere in the pesantren environment and the hearts of students. This study aims to find out how the tradition of reading al-Ma’tsurat in the Darul Qur'an Islamic boarding school; Second, to see how the meaning of al-Ma’tsurat is in the lives of the students of the Darul Qur'an Islamic boarding school; Third, to see the impact of reading al-Ma’tsurat on the students at Darul Qur'an Islamic Boarding School. This study uses the Living Qur'an method, where this method looks at how social phenomena are present because of the Qur'an in certain places and at certain times. From this study, it was found that the tradition of reading al-Ma’tsurat in Darul Qur'an is a daily activity that is routinely carried out in the morning and evening by the students. Al-Ma’tsurat has the meaning of a form of closeness to Allah and a form of gratitude for the blessings that Allah has given. Reading al-Ma’tsurat can have an impact both on the environment and on the mind of a student or reader.